Costs and effectiveness of community postnatal support workers: randomised controlled trial. Issue 7261 (9th September 2000) - Morrell, C Jane; Spiby, Helen; Stewart, P; Walters, S; Morgan, A
Abstract: Objectives: To establish the relative cost effectiveness of postnatal support in the community in addition to the usual care provided by community midwives. Design: Randomised controlled trial with six month follow up. Setting: Recruitment in a university teaching hospital and care provided in women's homes. Participants: 623 postnatal women allocated at random to intervention (311) or control (312) group. Intervention: Up to 10 home visits in the first postnatal month of up to three hours duration by a community postnatal support worker. Main outcome measure: General health status as measured by the SF-36 and risk of postnatal depression. Breast feeding rates, satisfaction with care, use of services, and personal costs. Results: At six weeks there was no significant improvement in health status among the women in the intervention group. At six weeks the mean total NHS costs were £635 for the intervention group and £456 for the control group (P=0.001). At six months figures were £815 and £639 (P=0.001). There were no differences between the groups in use of social services or personal costs. The women in the intervention group were very satisfied with the support worker visits. Conclusions: There was no health benefit of additional home visits by community postnatal support workers compared with traditional community midwifery visiting as measured by the SF-36. There were no savings to the NHS over six months after the introduction of the community postnatal support worker service.